Моделирование транзисторов с высокой подвижностью электронов - Emtsev, P. A. (PE "Politekhperiodika", Book and Journal Publishers, 2003)
The paper considers issues of modeling high electron mobility transistors (HEMT). The requirements for HEMT models are outlined. The most common types of models are described: small-signal, noise, nonlinear, and distributed. An algorithm for extracting parameters of the small-signal model is presented. References are provided to sources describing parameter extraction algorithms for noise and nonlinear models. Recommendations are given on choosing a transistor model for designing specific devices. The task of developing a universal model and introducing corresponding changes into software is formulated.